Waiting to Choose - Alex Imas; Michael A. Kuhn; Vera Mironova (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study the role of heuristic versus deliberative processing in intertemporal choice. Using studies in the Democratic Republic of Congo and an online labor market, we show that waiting periods –designed to prompt deliberation by temporally separating news about choice sets from choices themselves– can shift individuals away from decisions consistent with heuristic thinking and lead to substantially more patient choices. These findings are not captured by exponential or hyperbolic discounting. Additionally, waiting periods have larger effects on those shown to be particularly prone to myopia as a result of prior trauma, highlighting their potential as targeted interventions.
Keywords: D03; D90; C91; C93; 330; time preferences; waiting periods; heuristics; deliberation; field experiments